Analysis of the regulation and control of privatized home public services in Argentina under the Kirchner period (2003-2015) (2021)
This article studies the contractual renegotiations with the privatized companies, providers of electricity, gas, drinking water and basic telephony in the metropolitan area and Greater Buenos Aires (AMBA), as well as their regulatory regime and the evolution of the entities of respective control, during the presidential terms of Néstor Kirchner and Cristina Fernández de Kirchner, in order to analyze the “crossover” or “tension” between the “pro-market” policies promoted from the structural reforms of the 1990s, the original initiatives to change the regulatory institutional framework, the regulations finally approved and the consolidated - and long-standing - practices in the operation of the organizationsdedicated to supervising the functioning of these essential public services. . Under this framework, when analyzing the cycle of design and implementation of regulatory policies, it is noted that those measures that advocated the comprehensive review of contracts and the definition of new regulatory frameworks and control entities were bypassed, generating a greater provision, for internal and external factors, to enter into rate agreements with the concessionaires, without correcting the deficits in state capacity inherited from the previous stage. In this way, the opportunity - as recommended by CEPAL (2011) - to use regulation as a “policy instrument” capable of reversing the asymmetry of power between the State, privatized companies and users is lost.